Tinjauan Kriminologis terhadap Prostitusi Anak di Tangerang Selatan - Alexander; Muhammad Zaky (Anomie, 2022)
Child prostitution is the act of offering the services of a child to perform a toy act with an imbalance of money or a form of imbalance with someone or to anyone. Children's rights activists avoid using the term playing with children because it tends to have a negative connotation. The purpose of this study was to determine the background of the perpetrators of child prostitution. This study uses the theory of Routine Activities with qualitative research methods. This study concludes that there are actors who are motivated by their peers for the lifestyle reasons shown and seek satisfaction in biological relationships. In the activities of child prostitution perpetrators, perpetrators also get other benefits in the form of the economy even though that is not their main motive. One of the ways perpetrators carry out child prostitution activities is through applications on cell phones, this shows that one of the advancements in technology cannot be maximized properly and instead tends to be abused by child prostitution perpetrators.